Nickel allergy following European Union regulation in Denmark, Germany, Italy and the U.K. (10th October 2013) - Garg, S.; Thyssen, J.P.; Uter, W.; Schnuch, A.; Johansen, J.D.; Menné, T.; Belloni Fortina, A.; Statham, B.; Gawkrodger, D.J.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Nickel allergy affects 10–15% of women in the general population and is associated with hand eczema. Previous studies have shown a decrease in nickel allergy in young women in Denmark and Germany since regulations to control nickel release were implemented. What does this study add? Postregulation, a significant decrease in nickel allergy was seen in women with suspected dermatitis aged below 30 years in all four countries studied, and in men aged below 30 years in the U.K. and Germany, although an increase was seen in young Italian men. This study of 180 390 patients shows that the EU nickel regulations are starting to reduce nickel allergy in young men and women, although allergy remains prevalent and more work needs to be done to improve compliance with the regulations.